Liao Fan's Four Teachings in Islamic Perspective - Shofwan, Arif Muzayin (Journal of Islamic and Social Studies, 2025)
Liao Fan is a knowledgeable figure who taught four teachings to change the destiny of his son Yuan Tian Chi. This qualitative research with literature study analyzes four teachings of Liao Fan from an Islamic perspective. The data analysis technique uses content analysis by sorting things that are in accordance with the focus and objectives of the research. This study produces the following conclusions. First, building destiny from Liao Fan's advice is significant to the Islamic perspective on the concept of muallaq destiny, namely destiny that can be changed by humans according to the will of Allah SWT which is based on QS. Al-Baqarah verse 286 and HR. Ahmad. Second, how to change destiny from Liao Fan's advice with three factors, namely: knowing shame is significant to the content of HR. Hakim, HR. Bukhari, HR. Muslim, Turmudzi, Ibn Majah, and Baihaqi; fear (khauf) is significant to the content of QS. Ali Imran verse 175; determination and courage are significant to the content of QS. Ali Imran verse 159, QS. At-Thalaq verse 3, and QS. Al-Anfal verses 15-16. Third, making or collecting goodness from Liao Fan's advice with ten significant things with the contents of QS. Al-Hujurat verse 15, QS. Maryam verse 96, and several other verses of the Qur'an and hadith of the Prophet. Fourth, carrying out humility from Liao Fan's advice is significant in the contents of QS. Al-Furqan verse 63 and HR. Muslim.